The impact of the reputation of underwriter and sponsoring representative on IPO underwriting fees. Issue 4 (21st November 2016) - Chen, Chao; Wang, Xinrong
Abstract : Purpose: The purpose of this paper is to analyze the effect of the reputation of underwriters and sponsoring representatives on initial public offering (IPO) underwriting fees, and further investigates the role of ownership and political connection. Design/methodology/approach: The methodology includes three models. Model 1 empirically investigates the effect of underwriter's reputation on underwriting fee. Model 2 studies the effect of sponsoring representative's reputation on underwriting fee. Model 3 further examines the effect of underwriter's reputation and sponsoring representative reputation on the underwriting fee controlling for the impact of ultimate controlling ownership and political connection. Findings: The study documents that underwriters' and sponsoring representatives' reputation can result in reputational premiums. In the IPO of state-owned enterprises (SOEs), the reputation of underwriters and sponsoring representatives does not significantly affect the underwriting fees. In the IPO of non-state-owned enterprises (NSOEs), there is a significantly positive correlation between underwriters' and sponsoring representatives' reputation and underwriting fees. Further research results show that, on the one hand, the effect of underwriters' and sponsoring representatives' reputation on underwriting fees is not significant in the IPO of NSOEs with political connection. On the other hand, underwriting fees are positively associated with underwriters' and sponsoring representatives' reputation in the IPO of NSOEs without political connection. Research limitations/implications: The sponsoring representative's fee is not disclosed separately, which makes it difficult to distinguish the incremental effect from underwriter's services and reputation. Practical implications: NSOEs relative to SOEs are more likely to pay higher underwriting fees for hiring underwriter and sponsoring representative with better reputation during the process of IPO. Social implications: The reputation of underwriter and sponsoring representative does not matter to SOEs but does matter to NSOEs. However, NSOEs' political connection affects underwriter fees. Originality/value: This paper provides new evidence of sponsoring representatives' reputation and political connection on the underwriting fees in the IPO in Chinese SOEs and NSOEs.